Proceedings of the Second ACM/IEEE-CS Joint Conference on Digital Libraries - JCDL '02 2002
DOI: 10.1145/544229.544231
|View full text |Cite
|
Sign up to set email alerts
|

A graph-based recommender system for digital library

Abstract: Research shows that recommendations comprise a valuable service for users of a digital library [11]. While most existing recommender systems rely either on a content-based approach or a collaborative approach to make recommendations, there is potential to improve recommendation quality by using a combination of both approaches (a hybrid approach). In this paper, we report how we tested the idea of using a graph-based recommender system that naturally combines the content-based and collaborative approaches. Due… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
4

Year Published

2003
2003
2019
2019

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(61 citation statements)
references
References 6 publications
0
57
0
4
Order By: Relevance
“…However, the user studies had five and 19 participants, respectively, which led to statistically insignificant results. Three other studies reported contradicting results for offline evaluations and user studies (two of these studies had more than 100 participants) [57,93,117]. This means that offline evaluations could not reliably predict the effectiveness in the real-world use case.…”
Section: Offline Evaluationsmentioning
confidence: 98%
See 3 more Smart Citations
“…However, the user studies had five and 19 participants, respectively, which led to statistically insignificant results. Three other studies reported contradicting results for offline evaluations and user studies (two of these studies had more than 100 participants) [57,93,117]. This means that offline evaluations could not reliably predict the effectiveness in the real-world use case.…”
Section: Offline Evaluationsmentioning
confidence: 98%
“…The approaches extracted words from the title [79,85,112], abstract [26,51,61], header [43], introduction [57], foreword [57], author-provided keywords [26,57,58], and bibliography [27], as well as from the papers' body text [65,101,112]. The approaches further extracted words from external sources, such as social tags [58,62], ACM classification tree and DMOZ categories [91,94], and citation context [51,55,65].…”
Section: Content-based Filteringmentioning
confidence: 99%
See 2 more Smart Citations
“…A limitation of this work is the use of a single test collection. As future work, we aim at evaluating our approach on a different ER setting such as, for example, graph-based tag recommendation [9].…”
mentioning
confidence: 99%